Vloga diplomirane medicinske sestre pri umetni ventilaciji kritično bolnih pacientov - Štuhec, Marija (Obzornik zdravstvene nege, 2024)
ntroduction: Due to their inability to perform basic life activities, artificially ventilated critically ill patients represent the highest level of vulnerability and require the highest standards of nursing care. The aim of this literature review was to examine the role of the registered nurse in the artificial ventilation of critically ill patients.Methods: A review of the scientific literature was conducted in March 2022 in the PubMed, Cobbis and Sage Journals databases. The literature search was based on advanced keywords in English and Slovenian, namely: breathing; oral care; aspiration; pain; mobility. The search strategy was based on the following inclusion criteria: fully accessible texts, scientific journal, peer-reviewed publication, Slovenian or English language, period 2012–2022. The results were analysed using thematic analysis.Results: 15 relevant hits out of a total of 638 were included in the final analysis. The literature review included five observational studies, three cross-sectional studies, two phenomenological studies, one causal-comparative study, and four systematic literature reviews. The results were arranged into six categories: (1) quality nursing care, (2) oral care, (3) aspiration, (4) pain, (5) communication, and (6) mobility.Discussion and conclusion: The results show that the role of a registered nurse in the artificial ventilation of critically ill patients is complex and demanding. A registered nurse is expected to continuously train and adapt to current conditions, work under demanding conditions, and perform procedures and interventions that are an important part of high quality nursing care.
Keywords: aspiracija; aspiration; bolečina; breathing; dihanje; gibljivost; oral care; pain; ustna nega